2019
DOI: 10.1136/bmjopen-2018-023049
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital time and mortality in patients requiring a highest priority emergency medical response: a Danish registry-based cohort study

Abstract: ObjectiveTo examine the association between time from emergency medical service vehicle dispatch to hospital arrival and 1-day and 30-day mortality.DesignRegister-based cohort study.SettingNorth Denmark Region (≈8000 km2, catchment population ≈600 000).ParticipantsWe included all highest priority dispatched ambulance transports in North Denmark Region in 2006–2012.InterventionsUsing logistic regression and the g-formula approach, we examined the association between time from emergency dispatch to hospital arri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
(39 reference statements)
1
14
0
3
Order By: Relevance
“…In a Danish study on patients with dyspnoea, the 1-day mortality did not increase with a total transport time of > 30 min. However, for cerebrovascular conditions, a total at-the-scene time of > 60 min increased short-term mortality, suggesting faster transportation times in such cases [44]. A short at-the-scene time is essential for several conditions where definitive care is required in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In a Danish study on patients with dyspnoea, the 1-day mortality did not increase with a total transport time of > 30 min. However, for cerebrovascular conditions, a total at-the-scene time of > 60 min increased short-term mortality, suggesting faster transportation times in such cases [44]. A short at-the-scene time is essential for several conditions where definitive care is required in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MacKenzie et al showed in their study that, especially for the younger, more severely injured patients, treatment at a TC is not only more effective but also cost-effective, which underlines the importance of bringing the severely injured to a TC [23]. Studies show that especially the most severely injured patients, with ISS ≥ 25, hemodynamically instable and patients with severe traumatic brain injury (AIS ≥ 3), benefit the most from proper hospital triage, demonstrating lower mortality rates for these patients when brought to a TC [24][25][26][27]. Reducing under-triage should therefore be given priority.…”
Section: Discussionmentioning
confidence: 99%
“…Lansom and colleagues reported that prehospital intubation prolonged total prehospital time by 25 min, but shortened the time from arrival at the emergency department to the initiation of computed tomography imaging by 11 min [18]. In patients with heart disease, mortality was decreased to an adjusted odds ratio of 0.49-0.73 when total prehospital time was shortened [19]. Trauma mortality is decreased by shortening the scene time to < 50% of the total prehospital time [20].…”
Section: Discussionmentioning
confidence: 99%